Healthy eating habits - Reinke, Beth Bence (Minneapolis,MN : Lerner Publications, 2019)
Explore nutrition and healthful eating! Leveled text, colorful visual aids, and . . . photographs teach early readers about food, diet, and forming daily healthy eating habits.
Includes bibliographical references (page 24) and index.
2.3
K-3
400L
J
Keywords: Nutrition -- Juvenile literature; Food habits -- Juvenile literature; Health -- Juvenile literature; Nutrition; Food habits; Health